Optimizing Li‐Excess Cation‐Disordered Rocksalt Cathode Design Through Partial Li Deficiency. Issue 4 (16th December 2022) - Huang, Liliang; Zhong, Peichen; Ha, Yang; Cai, Zijian; Byeon, Young‐Woon; Huang, Tzu‐Yang; Sun, Yingzhi; Xie, Fengyu; Hau, Han‐Ming; Kim, Haegyeom; Balasubramanian, Mahalingam; McCloskey, Bryan D.; et al.
Abstract: Li‐excess disordered rocksalts (DRXs) are emerging as promising cathode materials for Li‐ion batteries due to their ability to use earth‐abundant transition metals. In this work, a new strategy based on partial Li deficiency engineering is introduced to optimize the overall electrochemical performance of DRX cathodes. Specifically, by using Mn‐based DRX as a proof‐of‐concept, it is demonstrated that the introduction of cation vacancies during synthesis (e.g., Li1.3‐ x Mn 2+ 0.4‐ x Mn 3+ x Nb0.3 O1.6 F0.4, x = 0, 0.2, and 0.4) improves both the discharge capacity and rate performance due to the more favored short‐range order in the presence of Mn 3+ . Density functional theory calculations and Monte Carlo simulations, in combination with spectroscopic tools, reveal that introducing 10% vacancies (Li1.1 Mn 2+ 0.2 Mn 3+ 0.2 Nb0.3 O1.6 F0.4 ) enables both Mn 2+ /Mn 3+ redox and excellent Li percolation. However, a more aggressive vacancy doping (e.g., 20% vacancies in Li0.9 Mn 3+ 0.4 Nb0.3 O1.6 F0.4 ) impairs performance because it induces phase separation between an Mn‐rich and a Li‐rich phase. Abstract : A new strategy based on partial Li deficiency engineering is introduced to optimize the electrochemical performance of Li‐excess cation‐disordered rocksalt cathodes. Both ab‐initio modeling and experiments show that the introduction of an appropriate amount of cation vacancies during synthesis can improve the Li percolation network and thus result in increased discharge capacity and rate performance.